Exploring Employees Job Performance of Small and Medium Size Enterprises (Journal of Informatics Education and Research, 2023)
Exploring employee job performance in (SMEs) is a critical endeavor to enhance the overall productivity and success of these organizations. SMEs often operate in resource-constrained environments, making it crucial to understand the factors that influence employee performance. By delving into various aspects such as leadership effectiveness, employee engagement, training and development opportunities, workplace environment, and the presence of effective performance appraisal systems, valuable insights can be gained. Through a combination of surveys, interviews, and data analysis, a comprehensive understanding of employee job performance can be achieved, enabling SMEs to implement targeted strategies for growth and improved competitiveness in their respective industries.